Transfer of Restrictive Episiotomy Practice with Low OASIS Rate from Tertiary to Primary Care Level—Lessons Learned and Future Challenges - Ingrid Marton; Matija Prka; Ana Tikvica Luetić; Domagoj Dokozić; Dubravko Habek; Sanja Rogina Curman; Zlatko Hrgović (Healthcare, 2026)
Introduction: For more than 40 years, obstetricians and midwives worldwide have continued to debate the significance of episiotomy and methods of reducing the rate of obstetric anal sphincter injuries (OASIS). Methods: A concise review of relevant recently published articles on obstetric perineal trauma was conducted, together with an analysis and comparison of the annual rates of episiotomy and OASIS (primary outcomes) at Clinical Hospital “Sveti Duh”, Zagreb (tertiary care level), and Požega General County Hospital, Požega (primary care level), over a ten-year period (2015–2024). Results: Routine (liberal) episiotomy has been abandoned in clinical practice worldwide, and restrictive (selective) episiotomy based on strict medical indications has gained widespread acceptance. Lateralization of episiotomy, slowing the expulsion of the fetal head, and manual perineal protection represent an important set of preventive interventions for avoiding OASIS. Restrictive episiotomy was implemented at Clinical Hospital “Sveti Duh” in 2010 and at Požega General County Hospital in 2012. A statistically significant difference in the episiotomy rate was observed between the two hospitals during the study period 2015–2019 (tertiary care level, 22.0% vs. primary care level, 17.5%), and an even greater difference was observed during 2020–2024 (tertiary care level, 31.0% vs. primary care level, 17.0%). At the tertiary care level, we detected a slight increase in the OASIS rate during 2020–2024 compared with 2015–2019, whereas a slight decrease was observed at the primary care level. No statistically significant difference in OASIS rates was detected between the two hospitals or between the two study periods, indicating that the OASIS rate remained stable at below 1%. Discussion: Nowadays, it is necessary to find a balance (when using mediolateral or lateral episiotomy) between an optimal overall episiotomy rate of